Quality Control of Dose Calibrators - Jain, A. N.; Rehman, M. Abdul (Nuklearmedizin - NuclearMedicine, 1981)
Radionuclide dose calibrators are instruments that require regular checks and proper usage to ensure that they are operating correctly. The responsibility for the accuracy of the activity and the resultant estimate of the dose delivered to the patient rests with the persons administering the radiopharmaceutical. Hence, it is essential that accurate measurements of radioactivity be provided by the dose calibrator in use in every nuclear medicine department. The routine testing of the calibrator would ensure the user that the overall characteristics of the instrument are within acceptable limits. The quality control of two dose calibrators was carried out elaborately and their performance was evaluated from various aspects of quality control such as geometry effect, instrument linearity, precision test, instrument accuracy etc. It was found that one of the calibrators was having non-linear response resulting in an error of 18% from the decay-predicted activity. It also showed a saturation effect beyond 310 mCi. Hence, it needed repair or recalibration. However, the other calibrator was working satisfactorily. This study also helped us in realizing certain operational pitfalls of the dose calibrators.